A case report on the treatment of diaphragmatic eventration-induced Budd-Chiari syndrome: the first innovative application of diaphragm plication - Jiming Ma; Bingjun Tang; Xuedong Wang; Liuqing Yang; Yumei Li; Yan Wen; Pengfei Wang (Frontiers in Medicine)
IntroductionBudd-Chiari syndrome (BCS) is a condition in which the hepatic outflow tract is obstructed. In some rare situations, abnormal diaphragmatic eventration (DE) is the main cause of BCS; furthermore, severe cases of DE-induced BCS can lead to liver congestion, functional impairment, and cirrhosis. Only three cases of DE-induced BCS have been reported in the literature to date, and no specific treatment modalities have been described. Herein, we present the first case in which minimally invasive surgery was used to treat the DE-induced BCS.Case reportA 72 years-old woman presented with hepatic encephalopathy as the first symptom and a diagnosis of cirrhosis. Contrast-enhanced computed tomography (CT) and abdominal ultrasound imaging revealed obstruction of the hepatic outflow tract, stenosis of the hepatic vein (HV) at the opening of the inferior vena cava (IVC) and dilatation of the lower segment of the IVC. These findings were consistent with a diagnosis of BCS. After three interventional balloon dilatations, the stenosis could not be resolved. Chest radiographs revealed a marked elevation of the right diaphragm (by approximately three vertebral levels) compared with the left diaphragm. During the thoracic surgery consultation, DE was diagnosed as a possible underlying cause of BCS, and diaphragmatic plication (DP) was proposed as a surgical treatment. The patient then underwent DP at our center and was discharged on postoperative day 4 without complications. The follow-up examinations revealed that the patient’s blood ammonia level and internal diameter of the IVC had returned to normal.ConclusionDiaphragmatic eventration is an exceedingly rare cause of BCS, and DP offers novel therapeutic insights for such condition. Etiology-driven strategies and appropriate multidisciplinary modalities are extremely necessary for diagnose and treat BCS.